Pengaruh Gratitude terhadap Life Satisfaction pada Pengguna Media Sosial Instagram - Nava Saliha; Lilim Halimah (UNISBA Press, 2023)
The use of social media Instagram in theory will have a positive effect on individual life satisfaction. But in reality only a small amount of influence is given, it can even be called a small influence. And when viewed from one of the determinants of individual life satisfaction is religion. With religion, individuals will be able to be grateful for their failures and lives and be able to increase their life satisfaction. The purpose of this study was to determine the gratitude and life satisfaction of Instagram social media users in young adults in the West Java region and to find out whether there is an effect of gratitude on life satisfaction on Instagram social media users in adulthood in the West Java region. This study uses a quantitative approach and data collection techniques using a questionnaire. The data analysis technique was carried out using the Simple Linear Regression Test. This study involved 193 respondents. The measuring instrument used in this study is The Gratitude Questionnaire-Six Item Form (GQ-6) which refers to the theory of McCullough, Emmons, and Tsang (2002) and Satisfaction With Life Scale which refers to the theory of Diener, Emmons, Larsen, & Griffin. (1985). The test results show that there is a significant effect of gratitude on life satisfaction. From these results, it can be said that there is an effect of gratitude on life satisfaction, but the effect is small. This is because there are other variables that can be mediators, such as research that has been done previously. Suggestions for further research are interested in choosing other variables that are more suitable for example social support variables, emotional difficulties and distributing questionnaires and the number of samples evenly. Penggunaan media sosial Instagram menurut teori akan memberikan efek positif terhadap life satisfaction individu. Tetapi pada kenyataannya hanya sedikit pengaruh yang diberikan bahkan bisa disebut memberikan pengaruh yang kecil. Dan jika dilihat dari salah satu faktor penentu life satisfaction individu adalah agama. Dengan agama individu akan bisa mensyukuri kegagalan dan kehidupannya serta mampu untuk meningkatkan life satisfactionnya. Tujuan penelitian ini untuk mengetahui gratitude dan life satisfaction pada pengguna media sosial Instagram pada emerging adulthood di wilayah Jawa Barat serta untuk mengetahui apakah ada pengaruh gratitude terhadap life satisfaction pada pengguna media sosial Instagram pada emerging adulthood di wilayah Jawa Barat. Penelitian ini menggunakan pendekatan kuantitatif dan teknik pengumpulan data dengan menggunakan kuesioner. Teknik analisis data dilakukan dengan menggunakan Uji Regresi Liniear Sederhana. Penelitian ini melibatkan 193 responden. Alat ukur yang digunakan dalam penelitian ini adalah The Gratitude Questionnaire-Six Item Form (GQ-6) yang mengacu pada teori McCullough, Emmons, dan Tsang (2002) dan Satisfaction With Life Scale yang mengacu pada teori Diener, Emmons, Larsen, & Griffin (1985). Hasil pengujian hipotesis menunjukkan bahwa terdapat pengaruh yang signifikan antara gratitude terhadap life satisfaction Dari hasil tersebut, dapat dikatakan bahwa ada pengaruh gratitude terhadap life satisfaction, namun pengaruhnya kecil. Hal tersebut disebabkan karena adanya variable lain yang bisa menjadi mediator, seperti penelitian yang sudah dilakukan sebelumnya. Saran penelitian selanjutnya yang tertarik bisa memilih variabel lain yang lebih cocok misalnya variabel social support, emotionally difficult dan menyebarkan kuesioner dan jumlah sampel secara merata.